Engagement Behavior Generation Z on TikTok Case Study: Cosmetic Brands - Cristy Natalia Lontoh; Faika Amelia Suyuthi; Julia Natassya Irena Christy Sagala (Budapest International Research and Critics University, 2022)
Indonesia is one of the countries that has an important role in the growth of digital globally. Data Reportal (January, 2020) reported that Indonesia is ranked third in the world as a country that has the largest number of internet users in the world. The number of internet users in Indonesia increased by 17 percent or worth 25.3 million users in a year. In addition, the Indonesian Internet Service Providers Association (APJII) also presented a survey that in 2019 to the second quarter of 2020 there has been an increase in the number of internet users in Indonesia which reached 196.7 million users. Various applications are available and accessed by the people of Indonesia. One of them is TikTok which also has a variety of content with a number of popular categories, such as comedy, street vlogs, fashion, makeup, lipsync, dancing and food. Based on searches on the TikTok app, the number of hashtags #makeup and #skincare has been viewed by 91.2 billion and 32.7 billion. This shows that TikTok is able to provide business opportunities for Cosmetic Products such as makeup and skincare in Indonesia. The study aims to test the relationship between marketing theory and its effect on TikTok's social media use with a quantitative approach and variable test. The results of this study show that TikTok social media users, especially generation Z, use TikTok social media in making decisions in determining the cosmetics they need.